2012
DOI: 10.1021/la300566x
|View full text |Cite
|
Sign up to set email alerts
|

DNA Electrochemistry with Tethered Methylene Blue

Abstract: Methylene blue (MB′), covalently attached to DNA through a flexible C12 alkyl linker, provides a sensitive redox reporter in DNA electrochemistry measurements. Tethered, intercalated MB′ is reduced through DNA-mediated charge transport; the incorporation of a single base mismatch at position 3, 10, or 14 of a 17-mer causes an attenuation of the signal to 62 ± 3% of the well-matched DNA, irrespective of position in the duplex. The redox signal intensity for MB′–DNA is found to be least 3-fold larger than that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
109
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(127 citation statements)
references
References 46 publications
17
109
1
Order By: Relevance
“…Electronic conductivity of redox metalloproteins and metalloenzymes 34,[36][37][38][39]55,56 , and of double strand DNA-based molecules [11][12][13][16][17][18][19]57,58 immobilized at electrochemical interfaces have been explored comprehensively. Electronic conductivity of "non-canonical" DNA forms, quadruplexes in particular have also been addressed, but such reports have only begun to appear much more recently [27][28][29][30][31][32][33] , and with little if any direct approach to interfacial ; (c) surface immobilized G-quadruplexes finally offer perspectives for ultra-sensitive detection of metal ions [40][41][42] , complex biomolecules such as peptides [23][24][25][26][27][28][29][30] , and perhaps other analytes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electronic conductivity of redox metalloproteins and metalloenzymes 34,[36][37][38][39]55,56 , and of double strand DNA-based molecules [11][12][13][16][17][18][19]57,58 immobilized at electrochemical interfaces have been explored comprehensively. Electronic conductivity of "non-canonical" DNA forms, quadruplexes in particular have also been addressed, but such reports have only begun to appear much more recently [27][28][29][30][31][32][33] , and with little if any direct approach to interfacial ; (c) surface immobilized G-quadruplexes finally offer perspectives for ultra-sensitive detection of metal ions [40][41][42] , complex biomolecules such as peptides [23][24][25][26][27][28][29][30] , and perhaps other analytes.…”
Section: Resultsmentioning
confidence: 99%
“…Electron or hole "hopping", with full vibrational relaxation between each single-charge hop has emerged as an attractive mechanism for photo-induced OGN electronic conductivity. This notion is, however, faced with challenges in interfacial electrochemical ET in redox marked surface immobilized OGN molecules [11][12][13][17][18][19][20] . Much lower energies than in photochemical ET are involved here, questioning the feasibility of actual electron or hole generation (reduction and oxidation) in the nucleobase pairs in the electrochemical potential ranges accessible.…”
Section: Introductionmentioning
confidence: 99%
“…In order to demonstrate that the electrocatalytically amplified signal is generated via DNA-mediated CT, the signal suppression due to the incorporation of a single-base mismatch was examined. Previously, the degree of signal attenuation upon incorporation of a single-base mismatch indicated that MB covalently tethered to the DNA duplex through a flexible ðCH 2 Þ 12 linkage can be reduced by both DNA CT and direct surface reduction (43). Here, we utilized a shorter ðCH 2 Þ 8 linkage in order to reduce contributions from the direct surface reduction of MB.…”
Section: Resultsmentioning
confidence: 99%
“…Amino-modified DNA, as well as thiol-modified DNA, was purified through standard procedures, as previously reported (6). MB modified with a terminal carboxylic acid was synthesized and coupled to the amino modified DNA (43). All single-stranded DNA was purified by reverse-phase HPLC and characterized with matrix-assisted laser desorption/ionization-time of flight (MALDI-TOF) mass spectrometry.…”
Section: Methodsmentioning
confidence: 99%
“…If both the amines of thionine are dimethylated, the product tetramethylthionine is known as famous MB. Detailed electrochemistry of such dyes are well documented in the literature and deoxyribonucleic acid (DNA) electrochemistry with tethered MB has received considerable interest (Pheeney and Barton, 2012). The electron transfer from the excited MB to graphene is more efficient than to GO, owing to the different electrostatic attraction between the dye and graphene.…”
Section: Immunosensing Procedures For Ceamentioning
confidence: 99%